Polanyi’nin Perspektifinden Sosyal Politikayı Okumak: Piyasa, Refah ve Emek Sorunsalı - Şenkal, Abdulkadir (Journal of Social Policy Conferences, 2022)
The Great Transformation, published in 1944 by Karl Polanyi, brought a new dimension to the relationship between market, state, and welfare. Polanyi considered the relation between markets and societies as a central feature of any social order; according to him, while the market destabilizes society, the commodification of labor, land, and money creates a reaction or “counter-movement.” For this reason, he describes market society as being a dominant principle for social organization. Social relations are embedded within the economic system instead of the economy being embedded in social relations. Polanyi also claims that market society is a political and social construct rather than a natural phenomenon. Yet, the rapid growth of government bureaucracy and interference in the private sphere has challenged many traditional notions related to the nature of capitalist society, especially since the 1940s. Therefore, the state plays an important role in both the establishment and regulation of the private market economy. This article proposes an interpretation, in the context of the contemporary welfare state based on Polanyi’s The Great Transformation, which discusses the distinction between market, welfare, and labor. The institutions, that once contributed to embedding the market economy within society, now play an important role in situations that have potential consequences for those seeking help from the welfare state.
Political Science
Keywords: double movement; emek; labour; refah; social policy; sosyal politika; welfare; Çifte Hareket

Devlet, Piyasa ve Toplum: Karl Polanyi ve Friedrich A. Hayek Üzerine Bir İnceleme - Güder, Mustafa; Atalay, Kürşad (İzmir İktisat Dergisi, 2022)
Individual life in general; It is determined by political, economic and sociological structures. The main forces that shape these structures are the state, market and society, respectively. When the views of Karl Polanyi and Friedrich Hayek on the state, market and society are considered comparatively, a holistic approach can be reached for understanding human life. In this context, the two thinkers have been the pioneers of two opponents lines in social sciences by putting forward opposite perspectives on the same phenomena. In the study, it is determined that these thinkers have a descriptive power in the ideological classification of later studies. Based on this, the views of the thinkers; It is put forward that it represents an "ideological pH value" for the social sciences. Polanyi draws attention that the ideals of individual freedom and equality claimed by the market system are not realized; brings social values to the fore.. Hayek claims that the market is the best institutional order that ensures human well-being and freedom. This study aims to discuss Hayek's free market view and Polanyi's embedded economic system with its political, economic and social aspects comparatively.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; devlet; market; piyasa; society; state; toplum